Penguatan Pendidikan Karakter berbasis revolusi Industri 4.0 untuk membentuk karakter Bangsa Indonesia - Sutarjo, J (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2021)
Moral decadence that occurs in society is a challenge for educational actors and shows that the goals of national education have not been fully achieved, especially in the aspect of noble character for the nation. In the Law Number 20 of 2003 concerning the National Education System, chapter 3 states that the purpose of national education is to develop the potential of students to become human beings who have faith and piety, have noble character, healthy, knowledgeable, capable, creative, independent, and become citizens. a democratic and responsiblity. To support the realization of national education goals, strengthening character education is carried out in the form of government regulations to revitalize and strengthen the potential and competence of educators, education staff, students, communities and the family environment. Strengthening national character education must also be carried out on non-educational aspects, such as efforts on economic aspects, law, role models, a conducive environment and elaboration with technological developments. In the aspect of education in Indonesia, we have carried out various reinforcements to strengthen the nation's character, including web-based learning, online student supervision, and online exams.